Estimation of Resting Energy Expenditure in Children With Spinal Cord Injuries - Patt, Pamela L (American Paraplegia Society, 2007)
BACKGROUND/OBJECTIVE: Resting energy expenditure (REE) is the amount of energy needed to maintain energy balance. Prediction equations exist to estimate REE for adults. Recommended dietary allowances (RDA) can be used to estimate energy needs for children but may not be suitable for children with spinal cord injury (SCI). Limited information is available on energy expenditure of children with SCI. Research is needed to determine a method to estimate energy needs for children with SCI. This research project was designed to determine REE in children with SCI who attended an SCI clinic at a children's hospital, determine variables that are correlated to REE in children with SCI, and determine a regression equation to estimate REE in children with SCI. METHODS: A sample of convenience was obtained from children attending the SCI clinic at Shriners Hospitals for Children–Chicago. The REE was measured after a 4-hour fast using a portable hand-held MedGem device to perform indirect calorimetry. Data including height, weight, age, months since injury, level of injury, gender, race, American Spinal Injury Association (ASIA) Motor Score, ASIA Impairment Score, and body mass index were obtained as covariates. RESULTS: Regression equations to predict REE were developed for boys and girls. The REE varied significantly from results obtained using both RDA and the Harris-Benedict equation. Height and level of injury were the only variables that correlated with REE in this sample. CONCLUSIONS: Measured REE was lower than the results of prediction equations. A regression equation was developed to estimate REE in children with SCI based on height and level of injury. Further validation studies are needed.